The ‘Firangi Mahal’: Family of the Learned and their Contribution to the Development of Islamic Educational Curriculum (Journal of the Asiatic Society of Bangladesh, Humanities, 2023)
The Firangi Mahal Family have consistently produced Islamic scholars, authors, mystics, politicians, and philanthropists for hundreds of years, making them the only family in the world to have done so. They stressed maqulat (rational science) rather than manqulat (transmitted science), and through this educational system, administrators, business people, poets, and writers were all adequately prepared for their relevant positions. Their most excellent intellectual outcome was the systemization of a new curriculum which, with improvements, has overtaken religious teaching in South Asia to the 21st century. This article will explain the Firangi Mahal family's contribution to knowledge advancement and their educational curriculum system. Data were obtained and examined from secondary sources, direct observation, and earlier research such as articles and journal publications. The results of this study show how committed this family is to serving humanity and how accepting they are of people. Furthermore, this study will assist in creating a comprehensive understanding of the evolution of Islamic curricula in the 18th and 19th centuries and the impact of the Dars-e-Nizami curriculum developed by Mullah Nizam Uddin Firangi Mahal in South Asia.Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 68(2), 2023, pp. 219-240